Pengembangan Google Sites Berbasis Inkuiri Terbimbing pada Materi Asam Basa sebagai Media Belajar Mandiri Siswa SMA/MA Kelas XI - Nurlatifah Nurlatifah; Jamil Suprihatiningrum* (Jurnal Pendidikan Sains Indonesia, 2023)
Technology-based learning media is currently relevant for implementing the "Merdeka" Curriculum because it offers many advantages. Google sites are one of the alternative technology-based media that can be used by students for independent, interactive, accessible, and not limited by space and time learning. This study aims to develop, determine the quality and responses of students to google sites acid-base material which is made referring to the guided inquiry model. Thiagarajan, Semmel Semmel’s 4-D (define, design, develop and desiminate) development model—which is limited to the develop stage—is used as a google sites development procedure. Seven respondents (one media expert, one material expert and five chemistry teachers) were involved to assess the quality of google sites through the expert judgment method with a four-scale questionnaire instrument and 10 students were asked to be willing to respond to google sites with a Guttman scale questionnaire sheet. The results of the quality assessment of google sites show that this media has an excellent category with a percentage of ideal quality of 95.83% according to the material expert; 92.5% by the media expert, and 95.68% by chemistry teachers. The response of students to google sites is also positive with the acquisition of an ideal percentage of 91%. The results of expert assessments and student responses indicate that google sites have a potential effect to be used as a chemistry learning medium, helping students understand concepts as well as interactive learning media